Membangun Kompetensi Kejuruan melalui Media Video Tutorial: Studi Empiris dalam Elektronika Dasar - Rahmanto, Abdul; Ranuharja, Fadhli; Muskhir, Mukhlidi; Karimi, Amir; Putra, Doni Tri Yanto (Lembaga Yasin AlSys, 2025)
This research is motivated by the presence of students who have very little desire to learn, grades that are still below the Minimum Completion Criteria (KKM) and the media used by teachers are still conventional such as printed books and whiteboards. The purpose of this study was to determine the effect of the use of video tutor media on student learning outcomes. The method used in this study is a quantitative method with the type of Quasi Experimental Design Nonequivalent Control Group with a two group pretest-posttest design. The sample determination uses a purposive sampling technique. Purposive sampling is sampling based on research objectives/certain characteristics. The population of class X TEI is 45 people. The number of samples is 24 students divided into 2, namely 12 students for the experimental class and 12 students for the control class. The research was conducted in the 2024/2025 academic year in class X majoring in industrial electronics engineering. This study shows that the average post-test score of experimental class students is higher than the post-test score of the control class, which is 92.00> 67.33. From the results of the Independent Sample t Test on the post-test data, the t-count value is obtained = 3.844 and the Sig. (2-tailed) value is 0.001. The t-table distribution value is seen based on df = 22 with a significant level of ???? = 0.05 is 2.074. Because the t-count value> t-table (3.844> 2.074) and Sig. (2-tailed) 0.001 <0.05, Ho is rejected and Ha is accepted. From the results of the independent sample T-test, video tutorial media has an effect on the learning outcomes of basic electronic engineering subjects for class X TEI at SMK Negeri 4 Pariaman.